The Concept of Indonesian State Income Distribution in terms of Concepts Al-Adl According to Baqir Al-Sadr - Hidayat, Salsa Addella Dyani; Izzati, Sya’na Sekar (DAS Institute, 2025)
This study aims to analyze the extent to which Baqir As-Sadr's concept of Al-Adl (justice) can positively impact the distribution of Indonesia’s state budget. The research employs a literature review and normative analysis of Islamic economic texts authored by Baqir As-Sadr. The findings indicate that while some efforts at redistribution through fiscal policies exist,not suitable with Al-Adl concept, implementing justice in income distribution in Indonesia still faces significant challenges in achieving the economic equality envisioned by the Al-Adl concept. This study is expected to contribute to Islamic economic discourse and provide an alternative perspective on creating a more equitable income distribution system in Indonesia. This study examines Indonesia's rising state revenue distribution, which still leaves a considerable portion of the population in poverty, with visible inequality. The analysis is conducted using Baqir As-Sadr's concept of Al-Adl. empirical, review (conceptual and viewpoints).